2014
DOI: 10.1097/ftd.0000000000000080
|View full text |Cite
|
Sign up to set email alerts
|

CYP3A5*3 and POR*28 Genetic Variants Influence the Required Dose of Tacrolimus in Heart Transplant Recipients

Abstract: Background: After heart transplantation (HTx), the interindividual pharmacokinetic variability of immunosuppressive drugs represents a major therapeutic challenge due to the narrow therapeutic window between over-immunosuppression causing toxicity and underimmunosuppression leading to graft rejection. Although genetic polymorphisms have been shown to influence pharmacokinetics of immunosuppressants, data in the context of HTx are scarce. We thus assessed the role of genetic variation in CYP3A4, CYP3A5, POR, NR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 35 publications
6
23
0
Order By: Relevance
“…Our study is the largest to date to evaluate the impact of CYP3A5 genotype on tacrolimus disposition in adult heart transplant recipients. We found that mean tacrolimus C 0 /D was 1.8‐fold lower and tacrolimus TDD was 2‐fold higher in CYP3A5 expressers vs non‐expressers, which is similar in magnitude to previous reports . In our cohort, CYP3A5 expresser status accounted for about 24% of the variability in tacrolimus C 0 /D, which is also consistent with other studies .…”
Section: Discussionsupporting
confidence: 92%
“…Our study is the largest to date to evaluate the impact of CYP3A5 genotype on tacrolimus disposition in adult heart transplant recipients. We found that mean tacrolimus C 0 /D was 1.8‐fold lower and tacrolimus TDD was 2‐fold higher in CYP3A5 expressers vs non‐expressers, which is similar in magnitude to previous reports . In our cohort, CYP3A5 expresser status accounted for about 24% of the variability in tacrolimus C 0 /D, which is also consistent with other studies .…”
Section: Discussionsupporting
confidence: 92%
“…The C/D ratio (ie, dose-adjusted drug C0) as an index of tacrolimus pharmacokinetics was used as an outcome variable. This ratio, defined as the drug C0 concentration per daily weightadjusted drug dose [(ng/mL)/(mg·kg -1 ·d -1 )], has commonly been used in other studies [25] . …”
Section: Methodsmentioning
confidence: 99%
“…17,18 Clinically, POR*28 may explain a part of calcineurin inhibitors (cyclosporine and Tac) variability, and POR*28 carriers may experience faster Tac metabolism. Indeed, it has been reported that POR*28 carriers have lower residual concentrations (C0) of cyclosporine and lower adjusted Tac C0 (Tac C0/Tac dose) in heart transplantation, 19 and adult 20,21 and pediatric 22 kidney transplantation. However, the strength of this association seems weak, 19,23 and the impact of POR*28 on Tac doses requirements is limited (15%-20%), compared with those mediated by CYP3A5 and CYP3A4 variants.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been reported that POR*28 carriers have lower residual concentrations (C0) of cyclosporine and lower adjusted Tac C0 (Tac C0/Tac dose) in heart transplantation, 19 and adult 20,21 and pediatric 22 kidney transplantation. However, the strength of this association seems weak, 19,23 and the impact of POR*28 on Tac doses requirements is limited (15%-20%), compared with those mediated by CYP3A5 and CYP3A4 variants. 21,23 Whether POR genotyping should be integrated in routine pharmacogenetic screening before Tac introduction in solid organ transplantation is not established, and the definite proof on the clinical impact of this polymorphism remains to be validated by independent large-scale studies.…”
Section: Introductionmentioning
confidence: 99%